The Quality of Web Sites' Health Information on Minimal Invasive Repair of Pectus Excavatum Using the DISCERN Instrument - Zuidema, Wietse P.; Graumans, Maarten J.; Oosterhuis, Jan W. A.; van der Steeg, Alida F. W.; van Heurn, Ernest (European Journal of Pediatric Surgery, 2020)
Introduction The Internet is a frequently used tool for patients with pectus excavatum (PE) to get information about symptoms and treatment options. In addition, it is used by both health care providers as a marketing tool and support group systems. The Internet health information varies in precision, quality, and reliability. The study purpose was to determine the quality of information on the PE Web sites using the DISCERN instrument, including information about operation and potential complications after a Nuss bar procedure.Materials and Methods Four search engines, Google, Yahoo, Ask, and Bing, were used to explore seven key terms concerning PE. Search language was English. The DISCERN quality instrument was used to evaluate the Web sites. Also, information on possible complications was scored per Web site.Results A total of 560 Web sites were assessed in March 2019. Excluded were 139 Web sites. There were 333 duplicates, leaving 88 unique Web sites. Of these, 58.1% were hospital-related information Web sites, 28.4% medical information Web sites, and 3.4% patient forum sites. Interactive multimedia was used on 21.6% of the sites. Pain postoperatively was mentioned on 64.8% of the sites, while only 9.1% mentioned the mortality risk of the surgical correction of PE for Nuss bar placement. The quality of the unique Web sites showed a mean DISCERN score of 42.5 (standard deviation 12.2). Medical information Web sites, encyclopedia, and government-sponsored sites had higher DISCERN scores. Hospital-related information sites, medical companies, and lay persons' sites, had lower total scores.Conclusion The overall quality of PE Web sites is low to moderate, with serious shortcomings.
Keywords: pectus excavatum; quality health information; DISCERN; pediatric surgery; internet